Helminth-induced regulatory T cells and suppression of allergic responses. (October 2018) - Logan, Jayden; Navarro, Severine; Loukas, Alex; Giacomin, Paul
Highlights: Infections with parasitic helminths (worms) may protect against development of inflammatory and allergic diseases. Helminths infections promote regulatory immune cell responses that may suppress detrimental allergic responses. Helminths elicit regulatory T cells via secretion of bioactive molecules or by altering the gut microbiota. Worms and their secreted molecules may be novel treatments for treating allergic inflammation. Abstract : Infection with helminths has been associated with lower rates of asthma and other allergic diseases. This has been attributed, in part, to the ability of helminths to induce regulatory T cells that suppress inappropriate immune responses to allergens. Recent compelling evidence suggests that helminths may promote regulatory T cell expansion or effector functions through either direct (secretion of excretory/secretory molecules) or indirect mechanisms (regulation of the microbiome). This review will discuss key findings from human immunoepidemiological observations, studies using animal models of disease, and clinical trials with live worm infections, discussing the therapeutic potential for worms and their secreted products for treating allergic inflammation.